Hyperhomocysteinemia as a Risk Factor and Potential Nutraceutical Target for Certain Pathologies - Tinelli, Caterina; Di Pino, Antonella; Ficulle, Elena; Marcelli, Serena; Feligioni, Marco (Frontiers in Nutrition, 2019)
Hyperhomocysteinemia is recognized as a risk factor for several diseases, including cardiovascular and neurological conditions. Homocysteine (HCys) is a key metabolite, involved in the biosynthesis and metabolism of methionine (Met), which plays a pivotal role in the physiological cells life cycle . The biochemistry of Met is finely regulated by several enzymes that control HCys concentration. Indeed, the balanced activity among the enzymes is essential for the cells wellbeing while its malfunction could raise HCys concentration which can lead to the onset of several pathological conditions . The HCys concentration increase seems to be mainly caused by the widely diffused polymorphisms of several enzymes. Nowadays, a blood test can easily detect the elevated concentration of HCys, referred to as Hyperhomocysteinemia (HHCys). A prolonged exposition to this condition can lead to the onset of cardiovascular diseases and can concur to the development of atherosclerosis, strokes, inflammatory syndromes like osteoporosis and rheumatism, as well as neuronal pathologies including Alzheimer’s and Parkinson’s diseases. In this review we analyzed the literature of several pathological conditions in which the molecular pathways of HHCys is involved. Interestingly, several observation indicates that the calibrated assumption of right doses of vitamins like folic acid, vitamin B6, vitamin B12 and betaine may control HHCys conditions.